The relationships between instrumented measurements of ankle and knee ligamentous laxity and generalized joint laxity - Pearsall, A. W.; Kovaleski, J. E.; Heitman, R. J.; Gurchiek, L. R.; Hollis, J. M. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The purpose of this study was to evaluate whether lower extremity joint laxity is a function of a particular joint and/or a generalizable characteristic (trait) of the person. Validated instrumented measurements of ankle and knee joint-specific laxity in the same individual were correlated to determine whether a relationship exists. In addition, ankle and knee joint-specific laxity were correlated with generalized joint laxity using the modified Beighton mobility index. Methods: Fifty-seven male and female athletes were studied. We examined dominant ankle laxity using an ankle arthrometer and dominate knee anterior laxity using the KT 2000. The dominant ankle was loaded in anteroposterior (AP) drawer and inversion-eversion (I-E) rotation. Laxity was measured as total AP displacement (millimeters) after ±125 N of applied force and total I-E rotation (degrees) was measured after ±4 N.m of applied torque. The dominant knee was loaded with an anterior drawer and laxity (millimeters) was measured after manual maximum displacement. Results: Non-significant correlations were observed among the test variables for generalized joint laxity (0.21 to 0.37; P>0.05) and instrumented ankle and knee joint laxity (0.19 to 0.21; P>0.05). When examined by gender, no statistically significant correlations (0.05 to 0.40; P>0.05) were found for either generalized laxity or instrumented ankle and knee joint laxity. Conclusion: These results imply that ankle and knee joint laxity are joint-specific and not generalizable.